2022
DOI: 10.3389/fcdhc.2022.831128
|View full text |Cite
|
Sign up to set email alerts
|

Elevated ACE Levels Indicate Diabetic Nephropathy Progression or Companied Retina Impaired

Abstract: ObjectivesRenin-angiotensin-aldosterone system plays important roles in the development of diabetic nephropathy (DN), and angiotensin converting enzyme (ACE) is the key factor in the process from angiotensin I to angiotensin II, but the variation and roles of serum ACE in DN patients are still unclear.MethodsForty-four type 2 diabetes mellitus (T2DM) patients, 75 DN patients, and 36 age-gender-matched healthy volunteers were recruited who attended Xiangya Hospital of Central South University in this case contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 41 publications
1
1
0
Order By: Relevance
“…The most obvious possibility is that ACE and ACE2, by regulating the levels of Ang II and/or Ang-(1-7) in pancreatic islets, are involved in the control of insulin secretion to the extent that blood flow is influenced by local levels of angiotensin peptides. This finding of our study is consistent with the previous research [19,20] and might be explained by the higher frequency of CHD in the diabetic population.…”
Section: Discussionsupporting
confidence: 94%
“…The most obvious possibility is that ACE and ACE2, by regulating the levels of Ang II and/or Ang-(1-7) in pancreatic islets, are involved in the control of insulin secretion to the extent that blood flow is influenced by local levels of angiotensin peptides. This finding of our study is consistent with the previous research [19,20] and might be explained by the higher frequency of CHD in the diabetic population.…”
Section: Discussionsupporting
confidence: 94%
“…Several clinical studies reported increased RAAS activity in patients with type 2 diabetes, especially in the presence of DKD (65)(66)(67)(68). RAAS hyperactivity has been well recognized as a critical pathogenetic factor contributing to progression of DKD and CKD towards advanced renal fibrosis and end-stage kidney disease (3).…”
Section: Effects Of Vasopressin On Reninangiotensin-aldosterone Syste...mentioning
confidence: 99%